Hubungan sikap kepada wang dan kepuasan kerja terhadap keinginan pekerja untuk berhenti secara sukarela: Kajian di sebuah organisasi pihak berkuasa tempatan berstatus bandaraya di Sarawak - Azman Ismail,; Mai Sumiyati Ishak,; Waty Kuching,; Mustaffa Omar, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
The notion of attitude towards money as a moderating factor in job satisfaction models is less emphasised in past studies. More important, further research in this area reveals that the effect of job satisfaction characteristics (i.e. extrinsic and instrinsic factors) on voluntary turnover is not consistent when attitude towards money is considered. Therefore, this study was conducted to examine the moderating role of attitude towards money in the relationship between job satisfaction characteristics and voluntary turnover. A survey research method was used and 93 usable questionnaires were gathered from employees who have worked in one city-based local authority in Sarawak, Malaysia. The outcomes of hierarchical regression analysis showed that interaction between attitude towards money and intrinsic job satisfaction factor had failed to reduce the inclination for voluntary turnover. On the contrary, the interaction between attitude towards money and extrinsic job satisfaction factor had suceeded in reducing the intention of voluntary turnover. This result indicated that attitude towards money did act as a partial moderating role in the job satisfaction model of an organisational sample. In addition, the implications of this study on job satisfaction theory and practice, methodological and conceptual limitations, as well as directions for future research are also discussed